Develop Islamic Waqf accounting in the light of IFRS - Nourine, Boumedienne; Henni, Mohamed Djaafar (Dirassat Journal Economic Issue, 2019)
Accountability has Increased on Islamic Waqf claims, in order to ensure transparency, disclosure and accountability and determine responsibility, and make sure Endowment Management restrict Sharia, laws and regulations, and standards of conduct, and the Islamic ethics and all private cessation controls, including contributing to the conservation endowment, assets and property, the rights of detained them and inspire confidence in the wakf, and creates a positive image about the community, and contribute to the protection of cessation of risks resulting from mismanagement. The study aims to develop a model for the interaction of accounting foundations and practices in the general framework of the management system in the waqf institutions to control their activities and ensure their proper use of the suspended funds. The study concluded that the proposed accounting model for the measurement and distribution of rents in waqf institutions achieves a clear disclosure of all the rules, bases and controls on which this model is based, thus raising awareness of the work of waqf institutions.